Temporal Trends in Mortality and Hospitalization Risk in Patients With Heart Failure According to the Hospital Frailty Risk Score - Noor K. Abassi; Nina Nouhravesh; Mariam Elmegaard; Marte Austreim; Deewa Zahir; Caroline Hartwell Garred; Jawad H. Butt; Camilla Fuchs Andersen; Jarl E. Strange; Caroline Sindet‐Pedersen; Daniel M. Christensen; Emil Fosbøl; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Heart failure (HF) and frailty often coexist. However, it is unknown how the interplay between HF and frailty at HF onset impacts prognosis of frail patients with HF and how this has evolved over time. Methods and Results We identified 131 235 patients with new‐onset HF (median age 74 years, 39.7% women) from Danish nationwide registers in 1999 to 2017. Stratification according to the Hospital Frailty Risk Score resulted in (1) 102 635 (78%) nonfrail, (2) 26 054 (20%) moderately frail, and (3) 2609 (2%) severely frail patients. The proportion of moderately frail patients increased from 13.2% to 24.9%. Five‐year absolute risks of all‐cause mortality, HF hospitalization, and non‐HF hospitalization were calculated using the Kaplan‐Meier and Aalen‐Johansen estimators. From 1999 to 2002 to 2003 to 2017, all‐cause mortality risk (95% CI) declined from 56.4% (55.8%–57.0%) to 33.3% (32.6%–34.1%), 79.8% (78.5%–81.0%) to 58.6% (57.2%–60.1%), and 90.8% (85.6%–96.0%) to 79.8% (76.4%–83.2%) in nonfrail, moderately frail, and severely frail patients, respectively. HF hospitalization risk remained almost constant over the study period. Non‐HF hospitalization risk declined from 74.0% (73.5%–74.5%) to 65.8% (65.0%–66.5%) in nonfrail patients and remained stable overall in moderately frail and severely frail patients over the study period. Conclusions We observed an increase in frail patients. Mortality decreased for all frailty groups but remained high for severely frail patients. These findings indicate the need for further evidence on the optimization of care for frail patients with HF, and future research should address the development of comprehensive management strategies, integrating frailty assessment into standard clinical care and focused care for older patients with HF.